Menyusun Dokumen Manajemen Supervisi Klinis di SMA Unggul Del Melalui Pendekatan “Sintesis Bukti Terbaik” : Studi Kasus Periode Tahun Ajaran 2021/2022-2022/2023 - Zandroto, Weni; Purba, Sukarman; Zainuddin, Zainuddin (Dharmas Education Journal (DE_Journal), 2024)
The purpose of this study was to develop a concept of clinical supervision management as a guideline for schools. This study aims to develop a clinical supervision management model in superior schools using the "Best Evidence Synthesis" approach. Through field surveys, interviews and synthesis of various studies and best practices in schools, this study formulated an effective, efficient, and contextual clinical supervision model. The sample of this study was the Teachers and Vice Principals of SMA Unggul Del. The results of the study indicate that the implementation of clinical supervision at SMA Unggul Del faces several significant challenges, including experienced teachers who are reluctant to be supervised, lack of time in planning supervision, and frequent conflicts between the teaching schedules of supervising teachers and the supervision schedule. Many experienced teachers are reluctant to undergo the supervision process due to a lack of understanding of the purpose of clinical supervision, which is often considered a performance evaluation, not an opportunity for professional development. To overcome this, school management needs to conduct comprehensive socialization regarding the benefits of supervision, including through workshops involving all teachers. In addition, the busy teaching schedule and other responsibilities make it difficult for teachers and supervisors to find the right time to carry out supervision. Solutions to this problem include the preparation of a supervision schedule that is integrated with the teaching schedule and the formation of a supervisory assistant team of senior teachers and administrative staff to assist in planning. Frequent clashes between teaching schedules and supervision schedules are also a challenge; therefore, it is important for school management to create an integrative calendar that lists all activities, as well as allocates specific time for supervision. With this comprehensive approach, it is hoped that the implementation of clinical supervision can run more smoothly and have a positive impact on the quality of education at SMA Unggul Del.